Therapeutic effect of Momordica balsamina leaf extract on ethanol-induced gastric ulcer in Wistar rats - Mshelia, Hamman Stephen; Karumi, Yagana; Dibal, Nathan Isaac (Annals of Research Hospitals, 2017)
Background: Momordica balsamina (M. balsamina) is an important medicinal plant that is used as an antibiotic, an anti-inflammatory and in the treatment of wounds. Its therapeutic properties suggest its alternative use in the treatment of various ailments and illnesses. Methods: Gastric ulceration was induced using 80% ethanol after a pilot study was done to identify which ulcer inducing agents would induce the most ulceration with minimal mortality in one hour. Thirty Wistar rats were divided into six groups of five rats each. Group 1 (control) was pretreated with normal saline, groups 2–5 were pretreated with 100, 200, 400, 800 mg/kg of M. balsamina extract, respectively, while group 6 was pretreated with 100 mg/kg ranitidine 1 h prior to administration of 80% ethanol. All the rats were sacrificed 1 h after the administration of 80% ethanol by cervical dislocation and the stomach were dissected, incised, washed and examined under dissecting microscope to assess the level of ulceration. Ulcerated and total areas of each stomach were measured in mm². The mean ulcer score, ulcer index and ulcer inhibition rate were calculated for each rat. Results: There was a significant dose-dependent decrease in the mean ulcer score of rats pretreated with M. balsamina compared to that of controls at P